THEORETICAL AND PRACTICAL ASPECTS OF THE INSTITUTIONAL DEVELOPMENT OF BANKING REGULATION AND SUPERVISION - Далгич, Каріна (Socio-economic relations in the digital society, 2020)
The article considers considers the institutional development of banking regulation and supervision in Ukraine, taking into account the progressive domestic and international experience in the article. Theoretical and practical aspects of the institutional development of banking regulation and supervision are revealed, the efficiency of the banking supervision and regulation system is analyzed in the context of introduction of a new institutional system of banking supervision in Ukraine, which would provide clear and effective supervision. The expediency of creating a single regulator of the entire financial market on the basis of the National Bank of Ukraine is considered, taking into account international experience. The main international trends in the implementation of Basel III and Basel IV are highlighted, as well as the main threats to the banking system of Ukraine are described. The IMF recommendations on improving the legislative and operational framework for crisis preparedness («The Financial Safety Net») are considered. A new institutional system of supervision has been proposed, which should include clear and effective supervision of consumer protection and the behavior of financial market participants. In parallel with the creation of a mega-regulator based on the National Bank of Ukraine (a single regulator of the financial market), it is proposed to create an independent institution for a consumer protection of financial services, which will cover the entire financial market and will have exclusive responsibility for consumer protection aw well as play a leading role in financial literacy initiatives. Once a new institutional system of supervision has been established, both functions (prudential and consumer supervisions) should be balanced and interact with each other to ensure the effective functioning of the supervision system.
Keywords: banking supervision and regulation; banking system; NBU; Basel; reforming; institutional development